Sa‘d al-dīn Ḥamūyeh’s sealer of the saints : Part I - Ballanfat, Paul (2025)
This paper intends to provide a first depiction of the question of the seal of sainthood in the thought of Saʿd al-dīn Ḥamūyeh (587-649/1191-1252) a prolific Sufi master who met with ibn ʿArabī in Damascus. His understanding of this notion starts most probably from his meetings with ibn ʿArabī. However, Ḥamūyeh tried to think it anew by articulating it with the prophetic narratives rather than the prophetic figures. The paper argues that the fundamental ground for thinking the seal of sainthood for Ḥamūyeh is time. This is why the seal is understood and named sealer-of-the-saints (khātim al-awliyā’) instead of seal of sainthood. The paper tries to show ultimately that the sealer-of-the-saints, whose name is Yasʿā according to Ḥamūyeh, is no other than the prophet who achieves his prophethood in his own sainthood.